The Euro Area Interbank Market and the Liquidity Management of the Eurosystem in the Financial Crisis - Achim Hauck; Ulrike Neyer (Verein für Socialpolitik, 2010)
This paper develops a theoretical model which explains several stylized facts observed in the euro area interbank market after the collapse of Lehman Brothers in 2008. The model shows that if transaction costs are high, banks with a liquidity deficit will prefer to borrow liquidity from the central bank rather than from surplus banks in the interbank market. This implies that the central bank assumes an intermediary function. From a policy perspective, we argue that possible measures of the Eurosystem to reactivate the interbank market may conflict, inter alia, with monetary policy aims.
Keywords: E52; E58; G21; 330; Liquidity; Monetary Policy Instruments; Interbank Market; Financial Crisis